Hipertensi Effect of Therapy Classic Music Mozart and Murotal Ar Rahman on Decreasing Systolic Blood Pressure in Women Hypertension - Ikit Netra Wirakhmi; Iwan Purnawan; Tin Utami (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2020)
The prevalence of hypertension in Indonesia still high. Safe and effective non-pharmacological therapy needed, namely Mozart music and Ar Rahman murotal. The research design was a Quasi Experimental with a Pretest-Posttest Control Group Design approach. The sample consisted of 40. Data were analyzed using t test and unpaired t test. The results : there was a decrease systolic blood pressure before and after treatment and  a significant difference in the mean reduction systolic blood pressure between the murotal group and mozart group. Conclusion : listening murotal Ar Rahman more effective to reducing systolic blood pressure hypertensive women than Mozart's music.